Bibliometric study of 'overviews of systematic reviews' of health interventions: Evaluation of prevalence, citation and journal impact factor. (25th October 2021) - Lunny, Carole; Neelakant, Trish; Chen, Alyssa; Shinger, Gavindeep; Stevens, Adrienne; Tasnim, Sara; Sadeghipouya, Shadi; Adams, Stephen; Zheng, Yi Wen; Lin, Lester; Yang, Pei Hsuan; Dosanjh, Manpreet; et al.
Abstract: Overviews synthesising the results of multiple systematic reviews help inform evidence‐based clinical practice. In this first of two companion papers, we evaluate the bibliometrics of overviews, including their prevalence and factors affecting citation rates and journal impact factor (JIF). We searched MEDLINE, Epistemonikos and Cochrane Database of Systematic Reviews (CDSR). We included overviews that: (a) synthesised reviews, (b) conducted a systematic search, (c) had a methods section and (d) examined a healthcare intervention. Multivariable regression was conducted to determine the association between citation density, JIF and six predictor variables. We found 1218 overviews published from 2000 to 2020; the majority (73%) were published in the most recent 5‐year period. We extracted a selection of these overviews ( n = 541; 44%) dated from 2000 to 2018. The 541 overviews were published in 307 journals; CDSR (8%), PLOS ONE (3%) and Sao Paulo Medical Journal (2%) were the most prevalent. The majority (70%) were published in journals with impact factors between 0.05 and 3.97. We found a mean citation count of 10 overviews per year, published in journals with a mean JIF of 4.4. In multivariable analysis, overviews with a high number of citations and JIFs had more authors, larger sample sizes, were open access and reported the funding source. An eightfold increase in the number of overviews was found between 2009 and 2020. We identified 332 overviews published in 2020, which is equivalent to one overview published per day. Overviews perform above average for the journals in which they publish.